The corporate social responsibility projects of the oil companies in Angola: anecdotal fact or significant new trend in public health development intervention? - Tallio, V. (Journal of Southern African Studies, 2015)
Angola is one of the most contradictory countries in the world. It has among the worst health and educational indicators, due to the war that tore it apart for more than 30 years. At the same time, it has one of the world's fastest rates of economic growth, thanks to the oil money that flows into the country. The country needs to (re)build its infrastructure - roads, schools, hospitals, and so on - and to develop its educational and health systems. Oil companies are deeply involved in this, through the process known as angolanizacao (Angolanisation). Through their corporate social responsibility (CSR) policies, they finance and implement social projects. They are thus replacing development NGOs, which never seized the market for the reconstruction of Angola. This article analyses the specificities of the oil companies' participation in the public health sector, looking at the changes their intervention is causing in the model of development. It concludes with an analysis of the consequences of these changes for the shape of the Angolan State.